Hubungan antara Kecemasan Karyawan Menghadapi Kemungkinan Pemutusan Hubungan Kerja dengan Kepuasan Kerja pada Karyawan Lepas - Aisyah, Nasrah; Widyastuti, Widyastuti (Indonesian Journal Publisher, 2024)
The purpose of this study was to determine the relationship between employee anxiety facing the possibility of termination of employment with employee job satisfaction. This research was conducted using a quantitative approach. This study used total sampling technique, 86 employees. The data collection technique was carried out by using a questionnaire. The measurement tools used are anxiety and job satisfaction scales with reliability values of 0,939 and 0,898. Data were analyzed using Spearman's Rho correlation analysis. The results show that the direction of the relationship between the two variables is inversely proportional or not unidirectional as the r value of -0,652. The effective contribution of employee anxiety about the possibility of layoffs to job satisfaction is 65.2%. Increased employee anxiety in facing layoffs will have an impact on decreasing job satisfaction, as well as a decrease in employee anxiety in facing layoffs will result in an increase in job satisfaction. Employee anxiety about the possibility of layoffs for freelancers at PT X Sidoarjo tends to be moderate, as well as job satisfaction for freelancers at PT X Sidoarjo is also moderate..